Complementary and Alternative Medicine Use in Women With Gynecologic Malignancy Presenting for Care at a Comprehensive Cancer Center. Issue 9 (November 2015) - Abdallah, Reem; Xiong, Yin; Lancaster, Johnathan M.; Judson, Patricia L.
Abstract : Objective: We evaluated complementary and alternative medicine (CAM) practices among women presenting to a National Cancer Institute–designated Comprehensive Cancer Center with a gynecologic malignancy. Methods: Women with a gynecologic malignancy who had consented to enrollment in our institutional prospective clinical registry between January 2003 and January 2014 and who had completed a questionnaire assessing sociodemographic characteristics, medical histories, quality of life, and CAM use were considered for analysis. Results: Among the 2508 women identified, responses to questions on CAM use were provided by 534 (21.3%). The majority of CAM question respondents were white (93.5%) and older than 50 years (76%). Overall, 464 women (87% of CAM question respondents) used at least 1 CAM therapy during the previous 12 months. The most commonly used CAM categories were biologically based approaches (83.5%), mind and body interventions (30.6%), and manipulative and body-based therapies (18.8%). The most commonly used individual CAM therapies were vitamins and minerals (78%), herbal supplements (27.9%), spiritual healing and prayer (15.1%), and deep breathing relaxation exercises (13.1%). Complementary and alternative medicine use was greatest in age groups 20 to 30 years and older than 65 years and was more prevalent among those who were widowed ( P < 0.005), retired ( P = 0.02), and with a higher level of education ( P < 0.01). There was no association with cancer type, race, or ethnicity. Conclusions: Complementary and alternative medicine use is common among women being treated for gynecologic malignancy. Given the potential interactions of some CAM modalities with conventional treatment and the possible benefits in controlling symptoms and improving quality of life, providers should discuss CAM with their patients. Abstract : Supplemental digital content is available in the text.